Automation of the driving task: Some possible consequences and governance challenges - Bryant Walker Smith (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
The possible consequences of the advent of fully automated vehicles (AVs) for personal transport are assessed. A shared-user model is considered preferable to an owner-user model; public-sector intervention is considered necessary to secure the successful integration of AVs with mass transit. Interurban expressways are found to offer a better opportunity than urban roads of capturing the vehicles' potential traffic and safety benefits. AVs' performance in a mixed-fleet scenario is highly dependent on segregation from other road users, but segregation poses significant challenges. The governance of a range of themes (such as demand management and security) is considered. In each case, challenges to achieving a socially desirable outcome are identified. Both laissez-faire and more interventionist styles of governance with respect to AVs present problems but laissez faire may carry greater risk. Decisions on governance should be based on meaningful dialogue with those who stand to be affected.
Keywords: 330; Kraftfahrzeug; Drohne; Mensch-Maschine-System; Stadtverkehr; Autovermietung; Verkehrsrecht